Translation Shift Of Noun Phrase In The Safe Movie And Its Subtitling - Utami, Melisa Setya; , Dra. Dwi Haryanti, M.Hum; , Siti Fatimah, S.Pd. M.Hum (2013)
This research studies on translation shift of noun phrase in the Safe Movie and its subtitling. The objectives of the research are to clarify the translation shift of noun phrase and to describe the equivalent translation of noun phrase in the Safe Movie and its subtitling. This research is descriptive qualitative research. The researcher uses documentation as the method of collecting the data. The data in this study are all sentences containing noun phrase found in the film entitled Safe Movie and its subtitling. The data source is English and Indonesian subtitling of movie the Safe Movie. The technique of analyzing data is comparing method. The result of this study shows that there are four shifts of translation found in this research. The writer finds level shift of translation in 23 or 12.23 % data of noun phrase into verb, 9 or 4.79 % data of noun phrase into adjective, and 2 or 1.06 % data of noun phrase into adverb. In the structure shift of translation there are 1 or 0.53 % data of noun phrase into verb phrase, 5 or 2.66 % data of noun phrase into adjective phrase, 1 or 0.53 % data of noun phrase into adverb phrase, 14 or 7.45 % data of noun phrase into prepositional phrase, 4 or 2.13 % data of noun phrase into compound noun, and 44 or 23.40 % data of noun phrase into noun phrase (commutation the pattern of sentence). In the intra - system shift of translation there are 14 or 7.45 % data of noun phrase into noun phrase (singular - plural) and 13 or 6.91 % data of noun phrase into noun phrase (plural - singular). In the category shift of translation there are 58 or 30.85 % data. In terms of translation equivalence, there are 113 data or 60.11% belongs to equivalent translation and 75 data or 39.89% belongs to non equivalent translation